Moral time - Black, Donald J. (New York ; Oxford : Oxford University Press, 2011)
Why do clashes of right and wrong occur? And why are some clashes worse than others? Here, Donald Black shows how changes in intimacy (friends or strangers?), inequality (rich or poor?) and cultural diversity (Christian or Jew?) all determine when conflict happens.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Social conflict -- Philosophy